Control Inventory of Raw Materials Using Supply Probabilistic with Q Method (Continuous Review Method) in the Animal Feed Industry Shrimp - Sihotang, Rinto; Handayani, Rina (Journal of Science Technology (JoSTec), 2024)
The ingredients used to make shrimp feed include soybean meal, shrimp head meal, squid flour, wheat flour, fish head meal, and other components. The demand for companies to produce shrimp feed varies and is unpredictable, leading to a shortage of raw materials and the inability to fulfill orders. To solve this problem, the company places special raw material orders or surprise orders. However, sudden orders result in higher inventory costs than normal company orders. This study aims to determine the optimal raw material order, to minimize inventory costs through a probabilistic model of raw material inventory control with the Q method (continuous review method). Based on the results of the Q method, optimal order quantity (q), reorder points (r), and safety stock (Ss) were obtained. The total inventory cost generated in the Q method was lower than the total inventory cost used by the company, with a total savings of 6.11% per year.